Application for Execution of Judgments Nos 2867 and 3003 Filed by SG. (2016) - Unknown
Abstract : 134 International organizations — Staff — Appeals mechanism — International Labour Organization Administrative Tribunal — Execution of judgments — Refusal by international organization to comply with earlier judgments — Award of interest for late payment — Award of moral damages — Imposition of penalties for any further delays